1999
DOI: 10.1046/j.1365-2214.1999.00127.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between lifestyle, social characteristics and obesity in 3‐year‐old Japanese children

Abstract: It has been observed that obese children receive genetic and environmental effects that are associated with them being overweight. With regard to the latter, lifestyles such as eating habits and physical activity have been focused on. In the present study, the social characteristics which would dominate their lifestyles were investigated as background variables. For this purpose, 9668 Japanese children aged three years who were all born in Toyama prefecture, Japan, in 1998, served as birth cohort subjects. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
102
1
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(112 citation statements)
references
References 19 publications
7
102
1
2
Order By: Relevance
“…Regarding international studies, Kagamimori et al 20 took the time children spend on outdoor play and sports as a measure of the level of physical activity, adopting time inferior to 60 minutes as the cutoff point to classify subjects with low level of physical activity. The results of an investigation with a cohort of almost 10 thousand 3-year-old Japanese children, showed a prevalence of 58.1% subjects classified with low level of physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding international studies, Kagamimori et al 20 took the time children spend on outdoor play and sports as a measure of the level of physical activity, adopting time inferior to 60 minutes as the cutoff point to classify subjects with low level of physical activity. The results of an investigation with a cohort of almost 10 thousand 3-year-old Japanese children, showed a prevalence of 58.1% subjects classified with low level of physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported a causal association between mother's employment and child obesity in Canadian 4 and American children 5 Meals were less frequent when mothers were employed in a Spanish study. 6 There was a higher incidence of child obesity among full-time employed Japanese mothers compared with non-employed mothers, 7 Other studies do not find any relationship between employment and non-employment 8,9 or report mixed 10 or no association between variation of dietary variables and maternal employment. 11 Takahashi et al 12 found a positive relationship between mothers' employment and children's probability of being overweight.…”
Section: Introductionmentioning
confidence: 96%
“…Furthermore, Japanese studies reported that irregular snacking had become more common in children, which may contribute to the increasing prevalence of obesity seen in children. [35][36][37] To our knowledge, no previous study has evaluated the effect of an irregular meal pattern on energy metabolism in adults. The purpose of the present study was to examine the effect of irregular meal frequency on energy expenditure and energy intake in healthy normal weight women.…”
Section: Introductionmentioning
confidence: 99%